Combustion aided by a glow plug in diesel engines under cold idling conditions - Li, Qile (2016)
Glow plugs are widely used to promote the desired cold start and post-cold start combustion characteristics of light duty diesel engines. The importance of the glow plug becomes more apparent when the compression ratio is low. An experimental investigation of combustion initiation and development aided by the glow plug has been carried out on a single cylinder HPCR DI diesel engine with a low compression ratio of 15.5:1. High speed imaging of combustion initiated by the glow plug in a combustion bomb has been used to add understanding of initiation process. Complementary CFD studies have been carried out using ANSYS Fluent 14.0 to explore the interactions between the glow plug and the spray behavior.